Is safe and effective LESS in benign adnexal diseases: A systematic review and meta-analysis. (2020) - Pan, Chunping; Zhao, Renfeng; Jiang, Yanming
Abstract: Objective: This meta-analysis aimed to evaluate the safety and efficacy of laparoscopic single site surgery (LESS) versus conventional laparoscopy (CL) for benign adnexal diseases. Method: Databases, including PubMed, Cochrane, Web of Science and Embase were searched to identify all articles published up to February 2020. We calculated the odds ratios and weighted mean differences (WMDs) with 95% confidence intervals (CIs) for dichotomous and continuous data. Results: This study included 8 RCTs, 12 retrospective studies and 6 prospective studies with a total of 2658 patients. We found the LESS had a shorter length of hospital stay (WMD = −0.24 [−0.34,  −0.13], I 2  = 48.6%), lesser postoperative pain 24 after surgery (WMD = −0.28 [ −0.51,  −0.05], I 2  = 72.3%), lower analgesic consumption (WMD = 0.45 [0.33, 0.61], I 2  = 46.9%), and better cosmetic outcomes than the CL group. A longer operative time (WMD = 0.18 [0.09, 0.28], I 2  = 35.2%), higher rate of postoperative complications (OR = 1.93 [1.09, 3.40], I 2  = 0.0%) was observed in the LESS group than in the CL group. Moreover, there was no significant difference in occurrence of wound infection, fever, ileus, estimated blood loss, intraoperative complications, and level of postoperative pain immediately, 6 h, 48 h after surgery between the LESS and CL groups. Conclusion: LESS may be safe and effective, option for the management of benign adnexal diseases. However, this novel technique has some disadvantages. Therefore, multicenter randomized controlled trials must be conducted to validate our findings. Highlights: Laparoscopic single-site surgery is a minimally invasive approach. Laparoscopic single-site surgery is faster recovery, lesser postoperative pain. Postoperative complications is similar in single-site and conventional laparoscopy. Laparoscopic single-site surgery may be safe and effective. It may be the preferred option for the treatment of benign diseases.